IMPACT OF OIL PRICE SHOCKS ON STOCK MARKET LIQUIDITY - Muhammad Usman; Raghab Majeed; Muhammad Umer (International Journal of Contemporary Issues in Social Sciences, 2024)
Oil prices may create direct impact into the real economy, by increasing the cost of firms and by decreasing the amount of disposal income that consumers have to spend. This study examines the impact of oil prices on the stock market liquidity in Pakistan. The main objective of this study to find the short run and long run impact of oil prices on stock market liquidity. This study measures the stock market liquidity by three proxies; first Amihud 2002 liquidity measures, second average value of share traded and third are trading volume. The independent variables include the exchange rate, inflation, oil production growth, consumer price index, oil prices, market volatility and stock market index. The final sample size for this research is 140 listed non-financial companies. The sample period for this research is 19 years from 2000 to 2019 on monthly basis. Study reports the results of unit root test, bound test, long run coefficient of ARDL, short run coefficient of ARDL along with diagnostic tests. Results show that oil prices and inflation has significant positive and negative impact on stock market liquidity. Oil production growth, real economic activity, market volatility and market index has significant positive relationship on stock market liquidity. Exchange rate has significant negative impact on stock market liquidity. Finally, study has policy implication for investor, regulators and all other stakeholder.